Plant cell wall signalling and receptor-like kinases - Wolf, Sebastian (Biochemical journal, 2017)
Communication between the extracellular matrix and the cell interior is essential for all organisms as intrinsic and extrinsic cues have to be integrated to co-ordinate development, growth, and behaviour. This applies in particular to plants, the growth and shape of which is governed by deposition and remodelling of the cell wall, a rigid, yet dynamic, extracellular network. It is thus generally assumed that cell wall surveillance pathways exist to monitor the state of the wall and, if needed, elicit compensatory responses such as altered expression of cell wall remodelling and biosynthesis genes. Here, I highlight recent advances in the field of cell wall signalling in plants, with emphasis on the role of plasma membrane receptor-like kinase complexes. In addition, possible roles for cell wall-mediated signalling beyond the maintenance of cell wall integrity are discussed.